PENGARUH PENAMBAHAN TEPUNG IKAN SAPU-SAPU (Lyposarcus pardalis) PADA PAKAN KOMERSIL TERHADAP PERTUMBUHAN IKAN PATIN (Pangasius sp.) Effect Addition of Fish Meal Sapu-sapu Fish (Liposarcus pardalis) on Commercial Feed for Growth Patin Fish (Pangasius sp.) - Denny Y Hutasoit; Eri Yusni; Indra Lesmana (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2015)
Patin is an economis fish, it is increasing demand for the sumatera people, however there is not an intensif cultivation. One of solved that problem needed the commercial feed as fish meal from the Lyposarcus pardalis where is high protein and good for the growth performance. These research has been studied from July until September 2014. The tested fish of 8 – 11 cm that fish were put in fiber sized 2 x 1 m by 9 units, with competely randomized design. The analysis statistic were used SPPS 21 and the results was calculate by Analysis of Variance (ANNOVA) and Tukey Test. Crude protein of 26% was better than the other crude protein, and the growth of body weight showed of 13,02 g, 4,16 cm for the length, specific growth rate (SGR) of 2,04% and food convention ratio (FCR) of 2,52.Keywords: Pangasius sp., Fish Meal Lyposarcus pardalis, Growth